Triglyceride to high-density lipoprotein cholesterol ratio was negatively associated with relative grip strength in older adults: a cross-sectional study of the NHANES database - Yan Huang; Jian Liao; Yang Liu (Frontiers Media S.A., 2023)
AimThis study aims to explore the association between triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio and relative grip strength in older adults in order to provide some references for the prevention and control of sarcopenia.MethodsFor this cross-sectional study, the demographic and clinical data of 1,404 individuals aged ≥60 years old were extracted from the National Health and Nutrition Examination Survey (NHANES) database in 2011-2014. The definition of relative grip strength was the sum of the largest reading from each hand/body mass index (BMI) ratio. We used weighted univariate linear regression and stepwise regression analysis to screen the covariates. Weighted univariate and multivariate linear regression analyses were used to explore the association between the TG/HDL-C ratio and the relative grip strength. We also explored this relationship in subgroups of gender, diabetes mellitus (DM), cardiovascular disease (CVD), and arthritis. The evaluation index was β with 95% confidence intervals (CIs).ResultsA total of 1,306 older adults were eligible. After adjusting for the covariates including age, gender, race, marital status, physical activity, DM, CVD, arthritis, and chronic kidney disease (CKD), we found that the TG/HDL-C ratio was negatively linked to the relative grip strength (all p < 0.05). Furthermore, the increased TG/HDL-C ratio was also related to the decreased relative grip strength in those who were women, not having DM, and having CVD (all p < 0.05).ConclusionWith the increase in the TG/HDL-C ratio, the relative grip strength of older adults decreased significantly, indicating that the TG/HDL-C ratio could be closely monitored in the older adult population and may be associated with the prevention and control of sarcopenia.